Learning Russian Language by Multimedia Resources - Urakovich, Khatamov Ildar (International Journal on Integrated Education, 2023)
Technology is the most useful resource in present time not for learners but also for engineers who are working at the factory. Without technology no future could be constructed in any domains of life. Learning Russian language by multimedia resource is very efficient way of building linguistic competences. Visuals are very important to watch and listen documentaries in Russian language. This paper highlights the essential ways of acquisition language by involving multimedia resources in the workplace or classes. The learners are able to acquire technical terminology through multimedia applications.